A Larger Root System Is Coupled With Contrasting Expression Patterns of Phosphate and Nitrate Transporters in Foxtail Millet [Setaria italica (L.) Beauv.] Under Phosphate Limitation - Ahmad, Zeeshan; Nadeem, Faisal; Wang, Ruifeng; Diao, Xianmin; Han, Yuanhuai; Wang, Xingchun; Li, Xuexian (Frontiers in Plant Science, 2018)
Foxtail millet [Setaria italica (L.) Beauv.], a widely cultivated food and fodder crop, develops a smaller root system while enlarges the root diameter facilitating nutrient transport under nitrogen limitation. How foxtail millet responds to phosphate limitation (LP) remains unaddressed. LP seedlings of the sequenced variety Yugu1 had significantly lower P concentrations in both shoots and roots and displayed higher levels of anthocyanin accumulation in leaves, indicating that the seedlings suffered from P limitation under hydroponic culture. One obvious and adaptive phenotype of LP plants was the larger root system mostly as the result of stimulation of lateral root proliferation in terms of the number, density, and length. Preferential biomass accumulation in the root under LP ensured carbon provision for root expansion and resulted in significant increases in the total and specific root length, which substantially extended the absorptive surface of P in the growth medium. Elevation of auxin and gibberellin concentrations might serve as an internal boost underpinning root architectural re-patterning under LP. Not just morphological adaptation, up-regulation of expression of SiPHT1;1 and SiPHT1;4 in roots and that of SiPHT1;2 in roots and shoots preconditioned adaptive enhancement of P uptake and translocation under LP. Interestingly, internal nitrogen surpluses occurred as indicated by dramatic increases in free amino acids in LP shoots and roots and higher concentrations of nitrogen in roots. Such nitrogen surplus ‘signals’ tended to switch down expression of nitrate transporters SiNRT2.1 and SiNAR2.1 in the root and that of SiNRT1.11 and SiNRT1.12 in the shoot to reduce nitrate mobilization toward or within the shoot. Together, our work provided new insights into adaption of a critical cereal crop to LP and its innate connection with nitrogen nutrition.